2006
DOI: 10.1530/rep.1.01088
|View full text |Cite
|
Sign up to set email alerts
|

Rho A/Rho kinase: human umbilical artery mRNA expression in normal and pre eclamptic pregnancies and functional role in isoprostane-induced vasoconstriction

Abstract: Pre eclampsia represents a state of increased or prolonged vasoconstriction, partially linked to the potent vasocontractile effect of isoprostanes. The process of Rho A-mediated calcium sensitisation is inherent to a state of prolonged contractility in many smooth muscle types. The aim of this study was (1) to investigate mRNA expression levels of Rho A and Rho kinase isoforms (I and II) in the umbilical artery from normotensive and pre eclamptic women and (2) to determine whether the effects of two isoprostan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 26 publications
0
12
1
Order By: Relevance
“…The importance of Rho in PE is supported by a study comparing subcutaneous resistance arteries from PE, Norm-Preg and nonpregnant women, and showing that Ca 2+ sensitivity of the contractile elements is increased in women with PE (VanWijk et al, 2002). Other studies have shown that mRNA expression of Rho-kinase is downregulated in umbilical arteries of PE women (Friel, 2006). Stimulation of AT 1 R may induce upregulation of RhoA/ROCK activity in hypertensive rats (Kataoka et al, 2002).…”
Section: Introductionmentioning
confidence: 90%
“…The importance of Rho in PE is supported by a study comparing subcutaneous resistance arteries from PE, Norm-Preg and nonpregnant women, and showing that Ca 2+ sensitivity of the contractile elements is increased in women with PE (VanWijk et al, 2002). Other studies have shown that mRNA expression of Rho-kinase is downregulated in umbilical arteries of PE women (Friel, 2006). Stimulation of AT 1 R may induce upregulation of RhoA/ROCK activity in hypertensive rats (Kataoka et al, 2002).…”
Section: Introductionmentioning
confidence: 90%
“…352 However, some studies show decreased expression of Rho-kinase in umbilical arteries of preeclamptic women. 359 …”
Section: Mmps and Vascular Dysfunction In Hypertensive Pregnancy Amentioning
confidence: 99%
“…Inhibition of Rho-kinase reduces TXA 2 -induced contraction in uterine vessels of non-pregnant rats [156]. However, some studies show decreased expression of Rho-kinase in umbilical arteries of PE women [191]. …”
Section: Introductionmentioning
confidence: 99%